2016
DOI: 10.1007/s11207-016-0923-0
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Solar X-Class Flares and CMEs: A Paradigm for Stellar Superflares and Eruptions?

Abstract: This paper explores the characteristics of 42 solar X-class flares that were observed between February 2011 and November 2014, with data from the Solar Dynamics Observatory (SDO) and other sources. This flare list includes nine X-class flares that had no associated CMEs. In particular our aim was to determine whether a clear signature could be identified to differentiate powerful flares that have coronal mass ejections (CMEs) from those that do not. Part of the motivation for this study is the characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 71 publications
7
69
0
3
Order By: Relevance
“…Previous findings of our earlier report, Harra et al (2016), and of event studies introduced in Section 1 are confirmed by the present comprehensive survey: the present work covers all on-disk flare events over a sixyear period including the cycle maximum without selection bias and extends the on-disk sample of Harra et al (2016) with the GOES peak brightness reaching down to M5 level, which is one virtue of this study 4 . In order to find the parameters that control the CME speed, we made scatter plots of V CME , similar to those in Section 3.2 but this time also of GOES parameters, τ FWHM , τ decay , and F SXR .…”
Section: Parameters That Determine Cme Propertiessupporting
confidence: 81%
See 2 more Smart Citations
“…Previous findings of our earlier report, Harra et al (2016), and of event studies introduced in Section 1 are confirmed by the present comprehensive survey: the present work covers all on-disk flare events over a sixyear period including the cycle maximum without selection bias and extends the on-disk sample of Harra et al (2016) with the GOES peak brightness reaching down to M5 level, which is one virtue of this study 4 . In order to find the parameters that control the CME speed, we made scatter plots of V CME , similar to those in Section 3.2 but this time also of GOES parameters, τ FWHM , τ decay , and F SXR .…”
Section: Parameters That Determine Cme Propertiessupporting
confidence: 81%
“…Although a general picture begins to emerge from these studies, each of them is based on a small sample of selected flares from different regions (some along with non-flaring counterparts) or on a small set of events from one target region. In a recent analysis, Harra et al (2016) used the set of X-class flares from the current solar cycle to show that there is no obvious difference in the flare duration between the eruptive and non-eruptive events and that the non-eruptive ones tend to have larger spot area. In this study, we expand the sample used by Harra et al (2016) by lowering the threshold to mid-M-class flares and by expanding the time interval (see Section 2.1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our new method of proton flux estimation due to stellar flares has important limitations, but it will be useful until advancements are made in the indirect detection of particles from stellar eruptive events (e.g., coronal dimming or Type II or III radio bursts; Crosley et al 2016;Harra et al 2016) or in our understanding of particle acceleration under kilogauss magnetic field strengths. The scaling relations are statistical and are relatively inaccurate for individual flares.…”
Section: Limitations Of the Methodsmentioning
confidence: 99%
“…The most energetic flares are commonly eruptive (Yashiro et al 2005), even though confined, non-eruptive X-class flares have been reported (Thalmann et al 2015;Sun et al 2015;Harra et al 2016) as well as CMEs with associated only C-class flares (Romano et al 2014;Chandra et al 2016). …”
Section: Introductionmentioning
confidence: 99%